Payment System Management to Prevent Fraud in Micro, Small, and Medium Enterprises (MSMEs) at Disa Olshop - Rudy Usman; Andi Indriani Ibrahim; Muh Riswandi Palawa; Dina Faidahlya Putri Setiawan; Sawitri Setiati Hamdani; Dhiza Syafitri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The development of e-commerce drives MSMEs to adopt digital payment systems, yet many still face fraud risks due to weak internal control mechanisms. This study aims to analyze how the payment system is managed by the MSME Disa Olshop in Palu City as a fraud prevention strategy. This research uses a qualitative approach with a phenomenological method, conducted through in-depth interviews with the business owner selected purposively. Data were analyzed thematically through transcription, coding, theme identification, and conclusion drawing. The findings indicate that the payment system remains manual and lacks verification technology, making it vulnerable to fraud such as fake transfer receipts. The absence of standard operating procedures and reliance on manual record-keeping increases the risk of financial loss. The business owner has acknowledged these weaknesses and is considering adopting digital systems such as QRIS and financial recording applications. This study concludes that strengthening the payment system through digital technology and internal controls is essential to prevent fraud and enhance consumer trust.